A river of names: The multiple voices of an Innu Riverscape. (20th October 2021) - Manikuakanishtiku,; Gagnon, Justine; Desbiens, Caroline; Kanapé, Éric
Abstract: Uamashtakan . Tekuatepeliu . Manishtikaushipu . Uashaupishkau . Manikuakanishtik u . I am a river of names. Like countless waterways around the world, I have been given a single official denomination—Manicouagan—by the State through the colonial renaming of land. Though the word Manicouagan derives from the original language of my People, the Pessamiulnuat (Innus of Pessamit), it carries a very small piece of my whole history and speaks with a monolithic voice. As an ancestral route connecting families to their hunting territories, each of my swirls and back eddies has something to say, witnesses to a longstanding and ongoing narrative. Going back to the meanings, practices, stories, and values that some of my People's denominations still bear, I wish to make myself heard differently from the voices that are both theirs and mine.